Anodic fabrication of advanced titania nanotubes photocatalysts for photoelectrocatalysis decolorization of Orange G dye. (February 2016) - Juang, Yaju; Liu, Yijin; Nurhayati, Ervin; Thuy, Nguyen Thi; Huang, Chihpin; Hu, Chi-Chang
Abstract: Titania nanotubes (TNTs) were fabricated on Ti mesh substrates by the anodizing technique. The effects of preparation variables, such as anodizing voltage, time and calcination temperature on the textural characteristics and photocatalytic activity of TNTs were investigated. The surface morphology, crystalline phase, and chemical composition were analyzed using field emission-scanning electron microscopy and X-ray diffraction. The photo-electrochemical properties of TNTs were examined by voltammetry. The TNTs were tested as a photoanode for advanced oxidation processes, such as photocatalytic, electrocatalytic, and photoelectrocatalytic decolorization of Orange G dye. The well-arranged TNTs electrode prepared in this work showed a high photocurrent density of 101 µA cm −2 at an optimum length-to-diameter aspect ratio of 31.2. In dye decolorization tests, the electrochemical photocatalytic system using TNTs as the photoanode achieved total decolorization and 64% mineralization under extended reaction time. These results show that TNTs prepared by this method is greatly stable in prolonged use and suitable as a photoanode in the photocatalytic/photoelectrocatalytic treatments of dye wastewater. Graphical abstract: Highlights: Successful fabrication of well-arranged TNTs photo-anode via anodizing. Application of the TNTs in photoelectrocatalysis (PEC) for dye wastewater treatment. The interrelationship of TNTs preparation condition, properties and PEC performance is examined. There is an optimum tube length-to-diameter ratio to produce highest photocurrent. Synergistic effect of photocatalytic and electrochemical process increases PEC efficiency.